Electronic circuits: a step-by-step approach using discrete semiconductor devices - Nair, B. Somanathan (Wheeler Publishing, 2000)
Electronic circuits: a step-by-step approach using discrete semiconductor devices / Nair, B. Somanathan. -- New Delhi: Wheeler Publishing, 2000 621.3815 N158 No. of Copies : 1